Association Between Femoral Component Sagittal Positioning and Anterior Knee Pain in Total Knee Arthroplasty: A 10-Year Case-Control Follow-up Study of a Cruciate-Retaining Single-Radius Design - Scott, Chloe E.H. (J Bone Joint Surg Am, 2019)
Anterior knee pain is the most common complication of total knee arthroplasty (TKA). The purpose of this study was to assess whether sagittal femoral component position is an independent predictor of anterior knee pain after cruciate-retaining single-radius TKA without routine patellar resurfacing. METHODS: A prospective cohort study of 297 cruciate-retaining single-radius TKAs performed in 2006 and 2007 without routine patellar resurfacing identified 73 patients (25%) with anterior knee pain and 89 (30%) with no pain (controls) at 10 years. Patients were assessed preoperatively and at 1, 5, and 10 years postoperatively using patient-reported outcome measures (PROMs), including the Short Form-12 (SF-12), Oxford Knee Score (OKS), and satisfaction and expectation questionnaires. Variables that were assessed as predictors of anterior knee pain included demographic data, the indication for the TKA, early complications, stiffness requiring manipulation under anesthesia, and radiographic criteria (implant alignment, Insall-Salvati ratio, posterior condylar offset ratio, and anterior femoral offset ratio). RESULTS: The 73 patients with anterior knee pain (mean age, 67.0 years [range, 38 to 82 years]; 48 [66%] female) had a mean visual analog scale (VAS) score of 34.3 (range, 5 to 100) compared with 0 for the 89 patients with no pain (mean age, 66.5 years [range, 41 to 82 years]; 60 [67%] female). The patients with anterior knee pain had mean femoral component flexion of −0.6° (95% confidence interval [CI] = −1.5° to 0.3°), which differed significantly from the value for the patients with no pain (1.42° [95% CI = 0.9° to 2.0°]; p < 0.001). The patients with and those without anterior knee pain also differed significantly with regard to the mean anterior femoral offset ratio (17.2% [95% CI = 15.6% to 18.8%] compared with 13.3% [95% CI = 11.1% to 15.5%]; p = 0.005) and the mean medial proximal tibial angle (89.7° [95% CI = 89.2° to 90.1°] compared with 88.9° [95% CI = 88.4° to 89.3°]; p = 0.009). All PROMs were worse in the anterior knee pain group at 10 years (p < 0.05), and the OKSs were worse at 1, 5, and 10 years (p < 0.05). Multivariate analysis confirmed femoral component flexion, the medial proximal tibial angle, and an Insall-Salvati ratio of <0.8 (patella baja) as independent predictors of anterior knee pain (R(2) = 0.263). Femoral component extension of ≥0.5° predicted anterior knee pain with 87% sensitivity. CONCLUSIONS: In our study, 25% of patients had anterior knee pain at 10 years following a single-radius cruciate-retaining TKA without routine patellar resurfacing. Sagittal plane positioning and alignment of the femoral component were associated with long-term anterior knee pain, with femoral component extension being a major risk factor. LEVEL OF EVIDENCE: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.